Assessment of knowledge on forensic anatomy among preclinical medical students - Manah Chandra Changmai,; Kastury Gohain, (Malaysian Society of Applied Biology, 2016)
Anatomy is one of the key disciplines in forensic science. The knowledge of anatomy is very important for a medical examiner or forensic expert. If there is any internal damage in the corpse and the forensic experts have no idea, then they may mistake it for a normal structure. In Malaysia, forensic anatomy is not included as a subdiscipline in the present preclinical medical curriculum. A preliminary study was undertaken to assess students knowledge on forensic anatomy and its scope. Primary data was collected through survey method from 66 students. A structured closed questionnaire was used to collect data from first year preclinical students of medical programme of International Medical School of Management and Science University. Majority of the students had knowledge on forensic anatomy and its scope. The students were aware of forensic anatomy and they had information on this subject from various website sources. The data was analyzed using SPSS version 20. The available results are discussed in the light of available literature. The results indicate the students are eager and enthusiastic in exploring the opportunity on learning more about forensic anatomy and its career prospects.